Treatable causes of fever among children under five years in a seasonal malaria transmission area in Burkina Faso - Francois Kiemde; Marc Christian Tahita; Palpouguini Lompo; Toussaint Rouamba; Athanase M. Some; Halidou Tinto; Petra F. Mens; Henk D. F. H. Schallig; Michael Boele van Hensbroek (BMC, 2018)
Abstract Background Fever remains a major public health problem. In Burkina Faso, more than half of febrile children are considered not to be infected by malaria. This study prospectively assessed probable (treatable) causes of fever in Burkinabe children. Methods A prospective study was conducted among febrile children (≥37.5 °C) under 5 years of age presenting at four health facilities and one referral hospital in rural Burkina Faso. From each participant, blood was collected for malaria microscopy and culture, urine for dipstick testing and culturing if tested positive for leucocytes and nitrite, stool for rotavirus/adenovirus testing, culture and parasitology, and a nasopharyngeal swab for culture. Results In total 684 febrile children were included in the study. Plasmodium falciparum malaria was found in 49.7% (340/684) of the participants and non-malaria infections in 49.1% (336/684) of children. The non-nalaria infections included gastro-intestinal infections (37.0%), common bacterial pathogens of nasopharynx (24.3%), bacterial bloodstream infections (6.0%) and urinary tract infections (1.8%). Nearly 45% (154/340) of the malaria infected children were co-infected with non-nalaria infections, but only 3.2% (11/340) of these co-infections could be considered as a possible alternative cause of fever. In contrast, in the malaria microscopy negative children 18.0% (62/344) of the infections could be the probable cause of the fever. Pathogens were not isolated from 23.7% (162/684) of the febrile cases. Conclusions Malaria remains the most common pathogen found in febrile children in Burkina Faso. However, a relative high number of febrile children had non-malaria infections. The correct diagnosis of these non-malaria fevers is a major concern, and there is an urgent need to develop more point-of-care diagnostic tests and capacities to identify and treat the causes of these fevers.